The Meaning of Pura Agung Surya Bhuvana on the Religious Lives in Jayapura in The Global Era - I Wayan Rai S; I Gusti Made Sunartha; Ida Ayu Made Purnamaningsih; Ni Made Ruastiti; Yunus Wafom (Humaniora, 2020)
The aim of the research was to be able to understand the meaning of the Pura Agung Surya Bhuvana for the harmony of religious life in Jayapura in the global era. Lately, people’s lives in Jayapura had been highlighted by frequent turmoil. The research problems were (1) why did non-Hindus in Jayapura often visit the Pura Agung Surya Bhuvana? (2) How did they understand the Agung Surya Bhuvana temple in this global era? The research applied a qualitative method. The data source was the life of a multicultural society in the Agung Surya Bhavana temple in the global era. The selected informants included the chairperson of Parisada Hindu Dharma Indonesia Jayapura, chairperson of Parisada Hindu Dharma Indonesia Papua, stakeholders, pengempon, penyungsung, and temple visitors both Hindus and non-Hindus who often come to visit the temple. All data collected through observation techniques, interviews, FGDs, and documentary studies that were analyzed interpretatively using religious theory, symbol theory, and structural-functional theory. The results show that (1) Non-Hindus in Jayapura often visit the Agung Surya Bhuvana temple because Hindus at the temple are very kind, friendly welcoming them, often involved in religious activities at the temple, for sightseeing, for meetings between residents. (2) The people in Jayapura in this global era interpret Agung Surya Bhuvana temple as a place of worship, a meeting place for religious followers, a place of art, a place to strengthen multicultural life (multiculturalism), and as a vehicle to strengthen national integration.